Validation of Oath in Family Law Issues - lila imanirad (فقه و حقوق خانواده)
Confession, testimony and explicity of oath is considered as the written documents to prove a claim according to the article of 1285 Civil Code. This research by descriptive-analytical method and collecting data and using a comparative approach addresses the validation of oath in family litigation and investigates if the oath in family litigation merely causes the discontinuance of the action or proves it as well. Findings shows, the role of oath seems not the same in all family lawsuits. The effect of oath in litigations concerning revocation of divorce, “Khol’” divorce, marriage portion, “Ila” and defects is permission for terminating the marriage, settling the dispute and discontinuing legal proceedings. In litigations concerning marriage relation and impotence, the lawsuits end with an oath taken by the denier. But if the denier abstains from taking an oath, the marriage relation and impotence is proved by the oath taken by the plaintiff. In alimony litigations, the oath of the losing party on insolvency or that of the winning party on solvency are considered as proofs. The effectiveness of oath in this case, which is limited to financial matters, proves the dispute in favor of the person taking the oath. Certainhy nature witness by enclosure oath must be considered witness or special reason. But it can not be considered as oath. Although there are many similarities between “La’an” and oath, La’an is not an oath. La’an is as method independent along witness and oath it has its own rules.the most items are revenue this reason for ihe seasof of hostility and drop the fight